FACTORS AFFECTING PARENTS' PARTICIPATION IN EDUCATIONAL MANAGEMENT OF WATLANBOON SCHOOL LATKRABANG DISTRICT OFFICE, BANGKOK - Rangsoi, Wassana (Journal of MCU Nakhondhat, 2021)
The objectives of this article were: 1) to study factors affecting parents' participation in educational management of Watlanboon school, Latkrabang district office, Bangkok; and 2) to compare opinions towards factors affecting parents' participation in educational management of Watlanboon school, Latkrabang district office, Bangkok that divided by personal characteristics. The qualitative research by us the questionnaires. Select purposive sampling such as: parents' of Watlanboon school for all 400 persons. Using analyzed with frequency statistics, percentage, average, standard deviation, t - test and F - test tested independent. And assumptions and table layouts. The research found that: 1) factors affecting parents' participation in educational management, it was at a high level ( = 3.85, SD = 0.87) divided into 3 areas such as: 1.1) extra curricular activities ( = 3.95, SD = 0.87), 1.2) teaching and learning management ( = 3.80, SD = 0.89), and 1.3) relationship between school and home ( = 3.79, SD = 0.86). And 2. Comparison of factors affecting parents' participation in educational management of Watlanboon school. By personal characteristics according to gender, age, economic status of the parents. And educational level of the parents The overall picture is no different. But in the age of parents in teaching and learning In organizing extra curricular activities And the relationship between school and home And the educational level of the parents in the field of teaching and learning And the relationship between school and home. The difference was statistically significant at 0.05. Nowadays, parents see the importance of taking part in the provision of education. In addition, a representative of the parents is selected and the role of the guardian is assigned to be the school committee. And keep parents informed of school news regularly.